1989
DOI: 10.1002/ijc.2910430619
|View full text |Cite
|
Sign up to set email alerts
|

Marker profile of mesothelial cells versus ovarian carcinoma cells

Abstract: We investigated the marker profile of human ascitic and cultured mesothelial cells, and compared it to that of ovarian carcinoma cells which are related in terms of their histogenesis, unrelated colon carcinomas being used as reference. Mesothelial and ovarian carcinoma cells could not be distinguished by (intermediate) filament typing, using monoclonal antibodies (MAbs) to keratins, vimentins and desmins. Colon carcinomas differed from mesothelial cells and ovarian carcinomas by the absence of keratin-7 filam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…However, since the initial report of Bast et al [3], several studies have demonstrated CA-125 positivity in the benign epithelium of the female genital tract, and also in the normal lung, serous membranes, various inflammatory processes, and malignant mesotheliomas [4,9,19,27,28]. In contrast, no CA-125 positivity was found in adult ovaries [37], and weak to negative staining was seen in cultured mesothelial cells [36]. Most of the above studies have not used antigen demasking of any kind, and the reported pattern of staining in these studies is either cytoplasmic or membranous.…”
Section: Discussionmentioning
confidence: 91%
“…However, since the initial report of Bast et al [3], several studies have demonstrated CA-125 positivity in the benign epithelium of the female genital tract, and also in the normal lung, serous membranes, various inflammatory processes, and malignant mesotheliomas [4,9,19,27,28]. In contrast, no CA-125 positivity was found in adult ovaries [37], and weak to negative staining was seen in cultured mesothelial cells [36]. Most of the above studies have not used antigen demasking of any kind, and the reported pattern of staining in these studies is either cytoplasmic or membranous.…”
Section: Discussionmentioning
confidence: 91%
“…31,37,38 The OV-TL 12/30 clone of CK7 antibody was described as a chain-specific monoclonal antibody that stains intermediate filament structures. 39 Moreover, OV-TL 12/30 antibody was found to specifically react with CK7 on electrophoretically separated cytoskeletal preparations (one-and two-dimensional immunoblots) of human cell lines. 40 Differences in the reactivity patterns of individual CK7 antibodies were explained as the likely result of epitope masking.…”
Section: Discussionmentioning
confidence: 98%
“…We have thus concluded that the increase in CA 125 in these breast cancer patients was caused by the metastatic infiltration of either the lung or the pleura: only in those patients with pleural involvement were CA 125 levels elevated; CA 125 levels in patients with no pleural involvement remained low. This hypothesis is further substantiated by reports indicating that CA 125 levels are elevated in patients with primary lung cancer predominantly when the pleura is affected (Niwa & Shimokata, 1986, Van Niekerk et al, 1989Kandylis et al, 1990;Kimura et al, 1990;Diez et al, 1991).…”
mentioning
confidence: 73%
“…Elevated CA 125 levels in primary lung cancer have been reported (Niwa & Shimokata, 1986;Van Niekerk et at., 1989; (0), liver (0) and lung (0) metastases, at the time of detection and thereafter. The CA 125 levels are shown only for those patients with elevated CA 125 levels at the time of detection of metastases.…”
mentioning
confidence: 99%